Colloidal Learning Design using Radec Model with Stem Approach Based Google Classroom to Develop Student Creativity - Aif Saiful Maruf; Wawan Wahyu; Wahyu Sopandi (Journal of Educational Sciences, 2020)
This study aimed to examine the feasibility of a RADEC model of colloidal learning design using the STEM approach based on Google classroom to increase student creativity. The method used was descriptive research. This study involved two experts, one teacher, and three high school students in Class XI.  Data was collected through an internal feasibility test, the suitability of the creativity sub-indicator with learning activities, and an external feasibility test carried out with a limited test to 3 high school students. The results showed that the learning design uses the RADEC model with a STEM approach based on Google Classroom that deserved to be used to increase student creativity. From this research it is concluded that this learning design can be used to increase student creativity.